FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU SEKS PRANIKAH PADA REMAJA DI MAN XI BEKASI - Rohani Siregar; Agustin S; Hartini Hartini (JOMIS (Journal of Midwifery Science), 2025)
Adolescence is a period of identity exploration and the urge to explore something new, often accompanied by deep curiosity. Free association during adolescence can have significant negative impacts, both in terms of health and psychology, especially among adolescents themselves. Premarital sexual activity refers to any form of sexual drive that is influenced by the urge to have intimate relationships that occur before marriage, either according to religious rules or legal provisions. The purpose of this study was to identify factors that influence premarital sexual behavior in grade XI students at MAN 1 Bekasi. The method used in this study uses a quantitative analytical method with a cross-sectional approach. The study sample consisted of 190 respondents who were randomly selected using the Slovin formula. Data analysis was carried out using a univariate and bivariate analysis approach using the chi-square statistical test. The results of the bivariate analysis indicated a significant relationship between knowledge (p-value = 0.000), attitude (p-value = 0.001), information sources (p-value = 0.008), parental role (p-value = 0.000), and peer influence (p-value = 0.008) with premarital sexual behavior in grade XI students at MAN 1 Bekasi in 2024. In conclusion, there needs to be an effort from the school to conduct socialization and education involving health workers about the dangers of premarital sexual behavior among students. And can support and help students to behave positively in accordance with existing norms.